The Relation between perception of social support with depression through self acceptance among people with type 2 diabetes - ., I Gede Nuarta; ., Didith Pramunditya Ambara, S.Psi.; ., Mutiara Magta, S.Pd. (Jurnal Pendidikan Anak Usia Dini Undiksha, 2013)
Diabetes Melitus (DM) is a chronic disease caused by metabolism disturbance in distributing glucose. People over 40 years old have increasing risk of suffering this disease. People with diabetes usually experience increase of glucose which triggers increase of cortisol, epinephrine, and norepinephrine which may cause depression. Depression experienced by people with type 2 diabetes is predicted be related to perception of social support and self acceptance. The purpose of this study was to examine the relation between perception of social support with depression through self acceptance among people with type 2 diabetes. This study involved 65 people with type 2 diabetes who were 40-75 years of age. The data was taken by using 3 measuring scales, which are: Perception of Social Support Scale, Self Acceptance Scale, and Depression Scale. Analysis technique used was Sobel Test mediation analysis. Result showed that there was significant negative relation between perception of social support and depression among people with type 2 diabetes, with coefficient regression of -0,1662; p=0,0095. Hypotheses 1 was accepted. There was significant positive relation between perception of social support and self acceptance among people with type 2 diabetes, with coefficient regression of 0,3132; p